Prema totalnom muzeju - Šola, Tomislav (Array, 2009)
The paper deals with a projection of museum and heritage profession which will in the future, as the author states, belong to an integral network of heritage institutions and will be based on a common theory. The will create a considerable profession whose activity will include collecting, care and communicating heritage. Therefore, total heritage will give rise to one strong profession, linked in the digital world which will function as a system which will have cumulative effects. Only such organized heritage can have an opportunity to create a profession and serve as cybernetic organism.